Radiation exposure in pediatric patients during micturating cystourethrography procedures. (November 2016) - Sulieman, A.; Babikir, E.; Alrihaima, N.; Alkhorayef, M.; Dalton, A.; Bradley, D.; Theodorou, K.
Abstract: The objectives of this study were to measure the entrance surface air kerma (ESAK) and the effective doses in pediatric patients undergoing micturating cystourethrography (MCU) procedures. The ESAK was determined using calibrated thermoluminescent dosimeters (TLD- GR 200 A) in 167 pediatric patients. The patient population was categorized into three groups according to age (0–5 years (group 1), 6–10 years (group 2) and 11–15 years (group 3)). The mean ESAK±SD and range (mGy) resulting from a MCU procedure was estimated to be 2.2±0.5 (0.8–9.2), 2.48±0.6 (0.9–8.1) and 3.90±0.6 (1.1–10.3) for group 1, 2 and 3, respectively. The mean effective dose was between 0.03 and 0.4 mSv per procedure for the pediatric population. Pediatric patients were exposed to avoidable radiation doses because no gonad shields were used. Highlights: Radiation dose measured for pediatric patients undergoing MCU procedure. Entrance surface air kerma (ESAK) were measured using calibrated TLD GR200A. Wide dose difference between ESAK suggests that optimization is not fulfilled yet. The dose delivered to the patient in MCU fell within the range of the most of previous studies.